2022
DOI: 10.1521/aeap.2022.34.4.272
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use as a Protective Factor Against Overweight in HIV-Hepatitis C Virus Co-Infected People (ANRS CO13 HEPAVIH Cohort)

Abstract: Overweight is increasingly prevalent in people living with HIV (PLWH), and is a high risk factor for metabolic disorders in this population. PLWH co-infected with hepatitis C virus (HCV) have a higher risk of metabolic disorders than their mono-infected counterparts. The putative relationship between cannabis use and body weight found in the general population has never been documented in HIV-HCV co-infected people. We tested whether cannabis use is associated with body mass index (BMI), overweight, and underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…A few studies have investigated the role of cannabinoids in the liver's health among PWH, with mixed results. The investigators of the ANRS CO13 HEPAVIH cohort demonstrated that, in the setting of HIV/HCV coinfection, daily cannabis use was negatively associated with being overweight [128], insulin resistance [129], and fatty liver, diagnosed by abdominal ultrasound [112] or the fatty liver index [113]. Oppositely, in 248 Russian PWH with heavy alcohol consumption, who were mostly male (72.6%), young (median age of 33.9 years), and coinfected with HCV (87.9%), Fuster et al did not report any association between cannabis use and advanced liver fibrosis (detected by FIB-4, aminotransferase-to-platelet ratio (APRI), or transient elastography) [114].…”
Section: Cannabinoidsmentioning
confidence: 99%
“…A few studies have investigated the role of cannabinoids in the liver's health among PWH, with mixed results. The investigators of the ANRS CO13 HEPAVIH cohort demonstrated that, in the setting of HIV/HCV coinfection, daily cannabis use was negatively associated with being overweight [128], insulin resistance [129], and fatty liver, diagnosed by abdominal ultrasound [112] or the fatty liver index [113]. Oppositely, in 248 Russian PWH with heavy alcohol consumption, who were mostly male (72.6%), young (median age of 33.9 years), and coinfected with HCV (87.9%), Fuster et al did not report any association between cannabis use and advanced liver fibrosis (detected by FIB-4, aminotransferase-to-platelet ratio (APRI), or transient elastography) [114].…”
Section: Cannabinoidsmentioning
confidence: 99%